Crecimiento de Istiophorus platypterus (Pisces: Istiophoridae) en la boca del Golfo de California - Alvarado-Castillo, Reyna (Universidad de Costa Rica, 1998)
Specimens (733) Istiophorus platypterus eaughl by sport fishing in the soulhern 01' the California Gulf were me¡lsured. The fourth  spine nI' the dorsal fin was collected to estimate the age and individuals from 1 to 8 years were found. The majority of lhe specimens were between 180 and 210 cm in lower jaw-fork length. The Bertalanffy growth ecuation estimrrted using length was: L,=203.6[ l_eo,ü+ooO';']. Growth was sllOwn to very fast in [he early years.